The extended minimum extraction technique: an update on sampling protocols - Hood, Amber G. E. (Ancient TL, 2022)
This paper communicates an update to the minimum extraction technique (MET) sampling protocol (a means by which to extract and subsequently measure a minute sample from museum objects for luminescence dating), designated the extended MET protocol. The new protocol facilitates a sample yield of approximately double that of the original MET protocol without altering the outward appearance of the sampling mark on archaeological materials. This development is useful when working with museum materials where the visual integrity of artefacts often takes precedence over access to sampling for luminescence analysis.